Influence of Apical Preparation Size and Working Length on Debris Extrusion - Silva,Emmanuel João Nogueira Leal (2016)
Abstract The aim of this study was to quantitatively evaluate the amount of apically extruded debris by single-file reciprocating instruments with different working lengths and apical preparation sizes. Eighty human single-rooted mandibular incisors were used and conventional access cavities were prepared. Then, the specimens were divided into four groups (n=20), according to root canal instrumentation: Reciproc size 25, .08 taper and Reciproc size 40, .06 taper instruments were used at the foramen; Reciproc size 25, .08 taper and Reciproc size 40, .06 taper instruments were used 1 mm short of the foramen. Distilled water was used as an irrigant and the apically extruded debris were collected in pre-weighted glass vials and dried afterwards. The mean weight of debris was weighed with a microbalance and statistically analyzed using one-way analysis of variance and the post hoc Tukey multiple comparison test (p<0.05). The results showed that all experimental groups were associated with debris extrusion. No significant difference was found in the amount of apically extruded debris among all experimental groups (p>0.05). The present study demonstrated that the working length and the apical preparation size did not have a significant effect on debris extrusion when performing single-file reciprocating instrumentation.